A human rights-based framework for qualitative dementia research - Diaz-Gil, A; Brooke, J; Kozlowska, O; Jackson, D; Appleton, J; Pendlebury, ST (SAGE Publications, 2023)
Background and objectives: People living with dementia have historically been excluded from qualitative research and their voices ignored due to the perception that a person with dementia is not able to express their opinions, preferences and feelings. Research institutions and organizations have contributed by adopting a paternalistic posture of overprotection. Furthermore, traditional research methods have proven to be exclusionary towards this group. The objective of this paper is to address the issue of inclusion of people with dementia in research and provide an evidence-based framework for dementia researchers based on the five principles of human rights: Participation, Accountability, Non-discrimination and equality, Empowerment and Legality (PANEL). Design: This paper adapts the PANEL principles to the research context, and uses evidence from the literature to create a framework for qualitative research in people with dementia. This new framework aims to guide dementia researchers in designing studies around the needs of people with dementia, to improve involvement and participation, facilitate research development and maximize research outcomes. Results: A checklist is presented with questions related to the five PANEL principles. These questions cover ethical, methodological and legal issues that researchers may need to consider while developing qualitative research for people with dementia. Conclusions: The proposed checklist offers a series of questions and considerations to facilitate the development of qualitative research in patients with dementia. It is inspired by current human rights work of recognized dementia researchers and organizations who have been directly involved in policy development. Future studies need to explore its utility in improving participation, facilitating ethics approvals and ensuring that outcomes are relevant to people with dementia.